TUHAN YANG AKAN DATANG DAN INISIATIF MANUSIA UNTUK PERUBAHAN DALAM SEJARAH MEMBACA DERRIDA BERSAMA KEARNEY - Paul Budi Kleden (Litbang STFT Widya Sasana Malang, 2010)
Jaques Derrida describes his philosophy as rightly pass for an atheist. However, he also uses the term what/whoever comes to point to God. For him God is the one who always in coming but never arrives and therefore there is nothing in the world and history that is able to represent God. This concept of absolute trancendendy arises the question about God’s immanency which is important to transform the world and history. Referring to Richard Kearney, a contemporary philosopher who creatively and critically intreprets Derrida, this article endevours to study the relationship between trascendency and immanency of God in the philosophy of Derrida.